2000
DOI: 10.1038/sj.leu.2401933
|View full text |Cite
|
Sign up to set email alerts
|

The amino terminus targets the mixed lineage leukemia (MLL) protein to the nucleolus, nuclear matrix and mitotic chromosomal scaffolds

Abstract: The mixed-lineage leukemia gene (MLL) is associated with more than 25 chromosomal translocations involving band 11q23 in diverse subtypes of human acute leukemia. Conditional expression of a 50 kDa amino terminal fragment spanning the AT hook motifs of MLL (MLL3AT) causes cell cycle arrest, upregulation of p21 Cip1 and p27 Kip1 and partial monocytic differentiation of the monoblastic U937 cell line, suggesting a major role for MLL3AT in MLL-AF9-induced myelomonocytic differentiation. In this study, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 62 publications
3
46
0
Order By: Relevance
“…This pattern has been reported by others using anti-AF4 antibodies. 36 This murine AF4 expression was always limited to the nucleus and was never cytoplasmic. This was in contrast to EGFP expression, which was seen in both the cytoplasm and nucleus, and appeared diffuse (Figure 2b).…”
Section: Control Of Af4 Subcellular Localizationmentioning
confidence: 93%
See 1 more Smart Citation
“…This pattern has been reported by others using anti-AF4 antibodies. 36 This murine AF4 expression was always limited to the nucleus and was never cytoplasmic. This was in contrast to EGFP expression, which was seen in both the cytoplasm and nucleus, and appeared diffuse (Figure 2b).…”
Section: Control Of Af4 Subcellular Localizationmentioning
confidence: 93%
“…The FLAG-MLL-AF4 construct was a kind gift of Masao Seto. Both the FLAG-MLL and FLAG-MLL-AF4 constructs were previously used by Hess et al 36 Inserts were generated either by PCR with high-fidelity Pfu polymerase, or by enzymatic excision from other plasmids. PCR inserts were sequenced to ensure proper orientation and correct sequence.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…We therefore hypothesized that other MLL chimeras might also rely on partner proteins for their association with p53. To facilitate the analysis of leukemic fusion binding to p53 in vivo, we generated an internal deletion in the MLL N terminus to eliminate specific sequences that mediate the strong association of MLL with chromatin and the nuclear matrix (8,9), which makes conventional binding assays nearly impossible (data not shown). Immunoprecipitation/Western blot analysis revealed that MLL fusion mutants strongly bound to p53 in vivo, thus indicating that intact partner proteins are sufficient for the association of MLL chimeras with p53 (Fig.…”
Section: Mll Fusions Suppress Transcriptional Activity Of Exogenous P53-mentioning
confidence: 99%
“…Infant pro-B acute lymphoblastic leukemia (ALL) harboring the fusion MLL-AF4 is characterized by a very brief latency and dismal prognosis, raising the question of how this infant cancer evolves so quickly [2,3]. Moreover, the exceptionally high concordance rate of this leukemia in monozygotic twin infants, approaching 100% [4], suggests that all the necessary genetic events required for leukemogenesis are accomplished prenatally [5].…”
Section: Introductionmentioning
confidence: 99%